15th Annual Fresno County Bar Association Judges' Dinner at Crossland's Barn - Watkins, Howard::::::::: (1983)
Truman Campbell playing clarinet, ? Playing saxophone, Robert Oliver playing trumpet, ? Playing trumpet, ?playing piano, ?playing bass fiddle